Pertumbuhan Dan Hasil Bawang Merah (Allium ascalonicum L.) Varietas Lembah Palu Padaberbagai Jarak Tanam Dan Dosis Pupuk Kandang Kambing - Normawati Normawati; Indrianto Kadekoh; Sakka Samudin (Mitra Sains, 2018)
Palu's local variety shallots are the main commodity of Central Sulawesi. However the productivity is still relatively low. This study aims to determine the best dose of goat manure on the growth and yield of shallots in the Palu Valley variety.The study conducted in the Village of Bulupountu Jaya, Sigi Biromaru District, Sigi Regency, from September to December 2015. The study used a randomized block design arranged in factorial two factors. The first factor is the spacing of 15cm x 15cm (J1) and 15cm x 20 cm (J2) while the second factor is the fertilizer dose consisting of P1 = 0 tons / ha, P2 = 10 tons / ha, P3 20 tons / ha, P4 = 30 tons / ha and P5 = 40 tons / ha. Thus there were 10 treatment combinations that were repeated 3 times so that there were 30 experimental plots. The observed variables included growth components and onion yields. The results of the study indicate that there was no interaction between spacing and dose of manure on growth and yield on most of the observed variables. Spacing does not significantly influence growth and yield. A dose of 30 tons of manure / ha provides better growth. The best production is obtained at the use of goat manure.